Acetalization of glycerol with benzaldehyde to synthesize 1,3-PDO via terminal hydroxyl group protection: An experimental and kinetic study - Mohammad Khan; Mohd Moiz Khan (Sustainable Chemistry for Climate Action)
The conversion of waste glycerol from biodiesel production into high-value-added chemicals is vital for promoting sustainable development within the Bio-Circular-Green Economy framework. The acetalization of glycerol with benzaldehyde was investigated using Amberlyst 15 as a catalyst. The resulting benzylidene acetals underwent dehydration and hydrogenolysis to synthesize 1,3-propanediol (1,3-PDO) through terminal hydroxyl group protection. Glycerol conversion reached 100%, yielding 47.8% of 5-membered and 51.3% of 6-membered acetals. Amberlyst 15 exhibited excellent activity and stability over five reuse cycles, ensuring a clean reaction without catalyst deactivation. However, higher catalyst loading, elevated temperatures, and increased mole ratios led to undesired side products, such as methyl-2-hydroxy-3-phenylpropanoate. The optimal conditions for synthesizing benzylidene acetals were determined to be a 1:1 molar ratio, 353 K, 5 wt.% catalyst, and 800 rpm stirring speed. Despite this, the new route was ineffective for 1,3-PDO synthesis. The overall reaction sequence was established, and the mechanism was effectively explained using a pseudo-homogeneous kinetic model.